Socially aware mobile application integrations in heterogeneous environments. (29th December 2014) - Chen, Donghua; Zhu, Xiaomin; Dai, Wei; Zhang, Runtong
Mobile web integration technologies and wireless sensor networks provide much more opportunities for human beings to interact with heterogeneous network environment including the communication network, the internet and sensor network. This paper investigates the integrated use of socially aware computing and data mining techniques through a mobile web application. It emphasises the study of regularity of human social activities through mobile applications in order to provide mobile users with intelligent assistance and support in the real world. The research investigates the effectiveness of single–layer and multi–layer evolutionary models of socially aware computing in order for these mobile web applications to be better integrated with the human social activities. Experimental analysis of our self–developed mobile platform as proposed from this research showed the superiority of socially aware computing when applied in the mobile field.